Transformasi Paradigma dalam Ilmu Pengetahuan dari Revolusi Sains Hingga Era Modern: Systematic Literature Review - Erniati (Journal of Innovation in Teaching and Instructional Media, 2024)
The journey of paradigm transformation in science begins with the scientific revolution of the 16th and 17th centuries and extends to the modern era marked by advancements in information technology. Utilizing a Systematic Literature Review (SLR) method, this study identifies factors influencing paradigm shifts, including technological advancements, globalization, and social needs. The findings indicate that paradigm transformation significantly impacts teaching methods, student learning approaches, and scientific research practices. Interdisciplinary approaches and the use of digital technology are becoming increasingly prevalent, while challenges such as resource limitations and resistance to change persist. This research aims to provide new insights into the integration of new paradigms in education and scientific research, along with their implications for educational quality in the modern era.